Association of messenger ribonucleic acid with 70S monosomes from down-shifted Escherichia coli. - Jacobson, L A (1976)
The complexed 70S ribosomes (monosomes) that accumulate in Escherichia coli after an energy source shift-down were examined in an electron microscope. In all cases, the ribosomes lie at or near one end of a ribonucleic acid (RNA) strand. This messenger RNA (mRNA) has a mean length of 168 nm and a length-average length of 200 nm, sufficient to code for polypeptides of a weight-average molecular weight of 20,000. The length distribution indicates that these strands are a reasonable representation of the population of monocistronic mRNA's of E. coli. The mRNA strands disappear entirely upon digestion with pancreatic ribonuclease, phosphodiesterase I, or polynucleotide phosphorylase. The susceptibility to digestion by 3'-exonucleases indicate that the ribosomes lie at the 5' end of the mRNA strands. These results are consistent with the hypothesis that down-shifted cells have a translational defect at a point subsequent to the binding of ribosomes to mRNA but prior to the formation of the first peptide bond, such that ribosomes remain bound at or near their points of initial attachment to mRNA.